Assessment of the Quality and the Susceptibility Profile of fungi in Peanut Butter Hawked in Lafia Metropolis - Orole, Olukayode Olugbenga (Biota, 2023)
Peanuts are a high-nutritional food source containing unsaturated fats, high-quality protein, carbohydrates, minerals and vitamins. The aim of the study was to determine the mycological quality of peanut butter consumed in Lafia and determine the antifungal susceptibility profile of fungal isolates. Peanut butter samples were collected from Lafia markets from which fungi were isolated, and the In vitro antifungal susceptibility profile was determined. The highest fungal count was from Shinge market (28.0x103 cfu/g), and the lowest from the College Village market (3.0x103 cfu/g). Of the fourteen fungal species isolated, genus Aspergillus had four species followed by genera Fusarium with three species. A. flavus was obtained from all the markets while A. carbonarius, A. versicolor, A. parasiticus, Alternaria alternata, Saccharomyces cerevisiae, Candida sp. and Trichophyton verrucossum were found in one market each. Antibiotics sensitivity test showed the highest inhibitory activity against F. graminearum and A. parasiticus from the Roundabout market (100% inhibition). Nystatin was the most effective antibiotic with inhibition of 1.87±0.23 cm against Alternaria alternata, and inhibiting all the isolates, while fluconazole was the least effective antibiotic tested. The study concludes that peanut butter consumed in Lafia has high concentrations of microorganisms making it unsafe for consumption.